The Influence of Firm Size, Leverage, and Corporate Social Responsibility on Firm Value (in Processed Food Sub-Sector Companies Listed on the IDX in the 2020-2024 Period) - Shanda Amarissa Purnomo; Rawi (Rescollacom (Research Collaborations Community), 2026)
This study aims to analyze the effect of firm size, leverage, and corporate social responsibility (CSR) on firm value in processed food sub-sector companies listed on the Indonesia Stock Exchange during 2020–2024. The research is motivated by fluctuations in firm value during the transition from the pandemic to the post-pandemic period. This study employs a quantitative approach with a causal associative design. The population consists of all processed food companies listed on the IDX, with purposive sampling resulting in 17 companies and 74 observations. Secondary data were obtained from annual reports and sustainability reports. Data analysis was conducted using multiple linear regression with SPSS. The results indicate that firm size has a positive but insignificant effect on firm value. Leverage also shows a positive but insignificant effect. Meanwhile, CSR has a significant negative effect and becomes the most dominant variable. Simultaneously, all independent variables explain 16.5% of the variation in firm value. The remaining variation is influenced by other factors outside the model.